The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1002/jts.21892
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Effects of Child Maltreatment in a War Region: Correlates of Psychopathology in Two Generations Living in Northern Uganda

Abstract: Adverse life experiences are a major risk factor for psychopathology. Studies from industrialized countries have consistently shown the detrimental effects of child maltreatment on the mental health of the victims. Research in war-affected populations, however, has mostly been restricted to the psychological damage caused by the war. Both war trauma and child maltreatment have rarely been studied simultaneously. In a comparative study of 2 generations living in severely war-affected regions in Northern Uganda,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 51 publications
4
23
0
Order By: Relevance
“…However this longitudinal study seemingly supporting the susceptibility hypothesis cannot rule out possible self-medication, since predeployment alcohol abuse may have developed as a consequence of self-medication secondary to earlier stressors (e.g., child maltreatment). Olema et al [ 39 ] examined two generations of northern Ugandans highly affected by war-trauma and child maltreatment and found both factors independently predicting symptoms of PTSD and depression in the young generation, but only child maltreatment remained a significant predictor in the guardian generation. They concluded that the impact of child maltreatment on mental health may outweigh the effects of war-related experiences.…”
Section: Introductionmentioning
confidence: 99%
“…However this longitudinal study seemingly supporting the susceptibility hypothesis cannot rule out possible self-medication, since predeployment alcohol abuse may have developed as a consequence of self-medication secondary to earlier stressors (e.g., child maltreatment). Olema et al [ 39 ] examined two generations of northern Ugandans highly affected by war-trauma and child maltreatment and found both factors independently predicting symptoms of PTSD and depression in the young generation, but only child maltreatment remained a significant predictor in the guardian generation. They concluded that the impact of child maltreatment on mental health may outweigh the effects of war-related experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Syrian refugees have described how war trauma and severe stress caused by poor living environments and uncertainty about the future made it difficult to maintain positive parenting strategies (El‐Khani, Ulph, Peters, & Calam, ). Longitudinal studies in Afghanistan, Sierra Leone, and Pakistan demonstrate the intergenerational transmissional impact of war, such as family violence, substance abuse and harsh parenting as only a few of the related consequences of war on family functioning (Betancourt, McBain, Newnham, & Brennan, ; Olema, Catani, Ertl, Saile, & Neuner, ; Panter‐Brick et al, ). These may compromise school aged children's physical and mental development in terms of complex cognitive and socioemotional abilities, including self‐esteem, self‐regulation skills and coping skills (Tol, Song, & Jordans, ).…”
mentioning
confidence: 99%
“… Eckart et al (2012) , in a PTSD-related neuroscientific study comprising mainly Kurdish adult refugees, found that adverse childhood experiences were associated with a negative effect on the hippocampus, possibly increasing vulnerability to the biological and psychological consequences of stress and PTEs later in life. More relevant to the present study, a two-generation study by Olema et al (2014) , involving 100 Ugandan adolescents and their parents, investigated the relative effects of war-related trauma versus experiences of child maltreatment in both generations. Both adolescents and adults were severely affected by both war-related trauma and childhood trauma, yet only maltreatment during childhood significantly accounted for PTSD in the parents.…”
mentioning
confidence: 99%